Assessment Literacy Profile of Science Teachers in SMAN 1 Gubug - Ipah Budi Minarti; Atip Nurwahyunani; Dewi Purichasari (International Journal of Research in Education, 2023)
Assessment is an integrated part of the planning and implementation process of learning. The transition from KTSP to the 2013 curriculum is a problem for teachers in applying assessment skills in learning, because teachers still have difficulty implementing authentic assessments and still use assessments in terms of cognitive tests only (Setiadi, 2016). This study aims to determine the literacy profile of science teacher assessments at SMA Negeri 1 Gubug and the assessment used by science teachers. This is because there is no source of research on teacher awareness of assessment in SMA Negeri 1 Gubug. This research uses descriptive quantitative research method, with purposive sampling. The instruments used in this research are the assessment literacy test, interview guidelines, questionnaires, and check list sheets. Based on the results of data analysis and discussion, it can be concluded that the assessment literacy profile of science teachers at SMA Negeri 1 Gubug is based on PAP Type II is in the "Very Low" category (assessment literacy questionnaire) and "Low" category (interview results). The teacher has the highest score with a score of 86% on the aspect of the difficulty of using the assessment, while the lowest score is on the aspect of attitude assessment by getting a score of 18%. The implication of this study is that by knowing the literacy assessment profile, teachers can understand and implement the importance of assessment so that this can be used as a benchmark in improving the quality of learning.